Factors influencing inhibition of glutamine synthetase enzyme in grass weeds by glufosinate ammonium under different temperatures - Mucheri, Tendai (Stellenbosch : Stellenbosch University, 2019)
Thesis (PhDAgric)--Stellenbosch University, 2019.